EMOTIONAL INTELLIGENCE AMONG DELHI-NCR MEDICAL STUDENTS: CONCEPT, PERFORMANCE CORRELATES, AND SCALE-BASED ASSESSMENT - Suneja, Ayushi; Shrivastav, Abha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In recent years, “Spotlight on Emotional Intelligence (EI)” has become bright, especially in the field of medical education where the clinical qualification is now spread beyond technical expertise to include emotional awareness, sympathy and mutual sensitivity. Medical professionals often face emotionally charged conditions, whether they are communicating bad news for patients or managing their own stress during an emergency. In such situations, EI becomes an important tool to navigate the human side of the drug. The purpose of this article is to find out the basic concepts of “emotional intelligence” and analyze its increasing relevance in the demand environment for medical training. The study specifically focuses on final year MBBS students from six medical institutions in Delhi NCR and evaluates their EI levels using the “Trait Emotional Intelligence Questionnaire (TEIQue).” The study, which used an enormous sample of 658 kids, found that students with higher EI levels did better in both the “classroom and the clinical setting”. In the education setting and the medical centre, subscales measuring consciousness of oneself, emotion management, and empathy were shown to be major predictors of efficacy.